Cross-Sector Collaboration as a Strategy to Mitigate the Ecological Impact of Election Implementation - Bahir Mukhammad; Megafury Apriandhini; Agus Iskandar Pradana Putra (Interdisciplinary Social Studies, 2025)
Simultaneous general elections throughout Indonesia can have a substantial environmental impact. The primary environmental challenge, which repeatedly causes problems, is the inadequate management of waste from campaign props. Waste management for campaign materials has not been specifically regulated, leading to policy inconsistencies across regions. Currently, managing waste from campaign props falls under the responsibility of Regional Apparatus Organizations, which process it for reuse where possible. Waste that cannot be reused must not be disposed of in Final Disposal Sites (TPA). The limited number of landfills and waste recycling sites in each region is insufficient compared to the volume of campaign props used in simultaneous elections. The Province of Bali took the initiative to implement green elections from the initial planning stage through to the end of election implementation. The General Elections Commission (KPU) urged contestants' campaigns to avoid plastic billboards, promoting social media and non-plastic alternatives instead. This green election initiative was realized through policies enacted by the Regional Government, including the Governor's Regulation on reducing plastic waste. It exemplifies cross-sector collaboration as a strategy to mitigate the ecological impact of election implementation. This study analyzes collaborative efforts and proposes policy recommendations for realizing green elections in Indonesia. This research employs a qualitative method with an empirical juridical approach, focusing on the implementation of green elections in Bali Province during the 2024 Regional Elections.